Novel chitosan derivative based composite scaffolds with enhanced angiogenesis; potential candidates for healing chronic non-healing wounds - Rizwan, Muhammad; Yahya, Rosiyah; Hassan, Aziz; Yar, Muhammad; Abd Halim, Adyani Azizah; Al-Maleki, Anis Rageh; Shahzadi, Lubna; Zubairi, Waliya (Springer Verlag, 2019)
The success of wound healing depends upon the proper growth of vascular system in time in the damaged tissues. Poor blood supply to wounded tissues or tissue engineered grafts leads to the failure of wound healing or rejection of grafts. In present paper, we report the synthesis of novel organosoluble and pro-angiogenic chitosan derivative (CSD) by the reaction of chitosan with 1,3-dimethylbarbituric acid and triethylorthoformate (TEOF). The synthesized material was characterized by FTIR and 13C-NMR to confirm the incorporated functional groups and new covalent connectivities. Biodegradability of the synthesized chitosan derivative was tested in the presence of lysozyme and was found to be comparable with CS. The cytotoxicity and apoptosis effect of new derivative was determined against gastric adenocarcinoma (AGS) cells and was found to be non-toxic. The CSD was found to be soluble in majority of organic solvents. It was blended with polycaprolactone (PCL) to form composite scaffolds. From an ex ovo CAM assay, it was noted that CSD stimulated the angiogenesis. [Figure not available: see fulltext.]. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.